Risk Factors of Perioperative Anxiety Levels in Sectio Caesarea Patients: A Cross-Sectional Study in Single Center, Bali, Indonesia - Anak Agung Angga Pringga Dana; Pontisomaya Parami; Kadek Agus Heryana Putra; I Gusti Agung Gede Utara Hartawan (HM Publisher, 2025)
Introduction: Anxiety is a prevalent emotional response in patients undergoing surgical procedures, including cesarean sections. Perioperative anxiety can negatively impact patient outcomes, affecting physiological parameters and postoperative recovery. This study aimed to identify the prevalence and risk factors associated with perioperative anxiety levels in patients undergoing cesarean section at Prof. Dr. I.G.N.G. Ngoerah Hospital, Bali, Indonesia. Methods: This cross-sectional study involved 37 patients scheduled for elective cesarean section at Prof. Dr. I.G.N.G. Ngoerah Hospital. Anxiety levels were assessed using the Perioperative Anxiety Scale (PASS), a validated instrument for measuring anxiety related to surgery. Data on sociodemographic characteristics, obstetric history, and medical history were collected through a questionnaire. Descriptive statistics and logistic regression analysis were used to analyze the data. Results: The majority of participants (59.5%) experienced mild to moderate anxiety levels. Age, occupation, education level, history of emergency surgery, previous surgical history, and gravidity were identified as potential risk factors associated with higher anxiety levels. Patients aged 25-29 years, housewives, those with a high school education, a history of emergency surgery, previous surgical experience, and primiparity were more likely to report mild to moderate anxiety. Conclusion: Mild to moderate anxiety is prevalent among cesarean section patients. Identifying risk factors associated with perioperative anxiety can aid healthcare providers in implementing targeted interventions to reduce anxiety and improve patient well-being.